MANAJEMEN PEMERINTAH KOTA PEKANBARU DALAM PENGEMBANGAN OBJEK WISATA DANAU BUATAN DI KOTA PEKANBARU TAHUN 2013 – 2014 - Yanti, Desi Nova; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Danau Buatan is one of tourism areas in Pekanbaru which is managed by PT Sarana Pembangunan Kota Pekanbaru as a BUMD and Pekanbaru City Government which aims to increase District Own Source Revenue of Pekanbaru City. But, in the implementation of Danau Buatan Area as a source of revenue cannot be realized well. Thus, it causes PT Sarana Pembangunan Kota Pekanbaru as the manager of this area to take some actions which one of them isconducting management. Management, according to Hasibuan, is a typical process consists of the actions of planning, organizing, activating and controlling which is conducted to determine and to achieve the goals that have been determined through the utilization of human resources and the other resources. This research aims to see the form of the management of Pekanbaru city government in developing Danau Buatan Tourism Object as District Own Source Revenue of Pekanbaru City.This research uses the qualitative research method with descriptive approach, which can be interpreted as a problem-solving process which is investigated by describing the condition of the research subject based on the facts that appear during the research and is continued based on existing theories. In management implementation, the government of Pekanbaru City together with PT Sarana Pembangunan Kota Pekanbaru conductthe four (4) principles of managementthat are Planning, Organizing, Directing or Actuating and Controlling. But the implementation cannot run optimally.Keywords : The Management of Pekanbaru City Government, Developing Danau Buatan Area, District Own Source Revenue